Factors that Contribute to the QTc Interval Prolongation in DR-TB Patients on STR Regimen - Tutik Kusmiati1 , Ni Made Mertaniasih2 , Johanes Nugroho Eko Putranto3 , Budi Suprapti4 , Desak Putu (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: QTc interval prolongation is one of the adverse drug reaction of several drugs used in DR-TBpatients treated with STR regimen. Drug-induced QTc prolongation can predispose patient to develop lifethreatening arrhythmia, increasing hospital length of stay and mortality. This study aims to determine factorsthat contribute to QTc prolongation in DR-TB patients on STR regimen.Methods. This was an observational retrospective study using medical records of DR-TB patients whoreceived STR regimen from August 2017 to March 2019 in tertiary hospital DR Soetomo, Surabaya,Indonesia. QTc interval was calculated by Fredericia formula. The influence of risk factors (age, bodyweight (BW), Body Mass Index (BMI), gender, comorbid, potassium, sodium and QTc baseline) with QTcprolongation was analyzed using multiple regression. The relationship between Moxifloxacin dosage andQTc was analyzed using Chi-Square test.Results Out of the 113 DR-TB patients who received the STR therapy regimen, 98 patients were eligible forthis study. They consist of 62 (%) male; 36 (%) female. Thirty-five (35,7%) of them had Diabetes Mellitusas a comorbid disease. The mean age of the patients was 44±11 years, with the mean of BMI was 20.20±3.73. Potassium and Sodium levels at the baseline were 4.192 ± 0.58 and 138.05 ± 4.562 respectively. TheQTc baseline before receiving STR regimen was 431.9±30,617ms. Patients received a dose of moxifloxacin400 mg (5.1%) , 600 mg (59,2%), and 800 mg (35,7%) according to body weight. There were no correlationbetween age, BW, gender, comorbid, and sodium baseline with QTc. There were correlation betweenpotassium (p=0,001), BMI (p=0,006) and QTc baseline (p <0,001) with QTc.Conclusion QTc baseline and potassium level are factors that contribute to the prolongation of the QTcinterval.